The First Thirty Years of the Country’s First Educational and Scientific Complex of Continuing Education: Achievements - Astakhova , K. (New Collegium, 2021)
The article analyzes certain aspects of the first three decades of activity of Kharkiv University of Humanities “People’s Ukrainian Academy”, the first private Ukrainian scientific and educational complex to implement the Lifelong Learning model. Such fields of concern as the contribution of the educational institution to the development of the country’s educational system, the impact on education reform, the study, analysis, development and implementation of social partnership, a new social function of education, are considered. Special attention is paid to the necessity of drawing on the practices and experience of innovative educational structures that emerged in the early 1990s in Ukraine as a result of dramatic political and socio-economic changes. Moreover, the study of both best practices and those experiments and innovations that fell short of expectations without resulting in a decrease in quality given their small scale is underlined.